The clinical features of COVID-19 patients with positive viral RNA stool test results and possibility of fecal-oral transmission : A Systematic Review - Selina Natalia; Felicia Imanuella Thorion; Luky Adlino; Clifford Eltin John; Andree Kurniawan; Nata Pratama Hardjo Lugito (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Objective : Coronavirus disease 2019 (COVID-19) has been declared as an international public health emergency by the World Health Organization (WHO), with outbreaks in over 200 countries and causing over 390,000 deaths globally. ACE-2 receptors are highly expressed in the upper and lower gastrointestinal system, providing a prerequisite for SARS-CoV-2 infection in the gastrointestinal tract. In addition, over half of the COVID-19 patients have viral nucleic acid detected in their feces and almost one-quarter of the cases, the stool samples test positive even when respiratory samples are negative. The aim of this systematic review is to summarize literature and to evaluate the clinical characteristics of patients with positive viral RNA stool test for COVID-19 and if there is a possibility of fecal-oral transmission of SARS-CoV-2 virus.Method : This systematic review has been registered in PROSPERO (CRD42020183049). A systematic search of the literature for observational study and randomized control trial was conducted in PubMed central and Google Scholar through May 5th, 2020. Three reviewers independently searched and selected. The risk of bias was evaluated using Newcastle-Ottawa Quality assessment tool.Results : 340 articles were screened, then from which eight articles were selected. Of eight articles that were included in this study, we sought for three main categories of the clinical manifestation; gastrointestinal, respiratory, and others. Each study was reviewed systematically to gain demographic data and evidence regarding the possibility of fecal oral transmission in SARS-CoV-2. Two studies reported prolongation of positive stool test results after the respiratory specimen conversion to negative which support the theory of fecal oral transmission.Conclusion : In conclusion, diarrhea, cough, and fever are the most common clinical manifestations in COVID-19 patients with positive RNA stool test results. Fecal oral transmission may be possible due to the ACE-2 receptors in the lining of the gastrointestinal tract. RNA stool test should be used as addition in discharging COVID-19 patients.